Influence of Physical Effects on the Swarming Motility of Pseudomonas aeruginosa - Yang, Alexander; Tang, Wai Shing; Si, Tieyan; Tang, Jay X (Biophysical journal, 2017)
Many species of bacteria can spread over a moist surface via a particular form of collective motion known as "surface swarming". This form of motility is typically studied by inoculating bacteria on a gel formed by 0.4-1.5% agar, which contains essential nutrients for their growth and proliferation. Using Pseudomonas aeruginosa and its pili-less mutant, ΔPilA, we investigate physical factors that either facilitate or restrict the swarming motility, measured by the rate of increase in area covered by a spreading bacterial colony, i.e., a swarm. The wild-type colony spreads over the agar surface in highly branched structures. The pili-less mutant fills up the area more fully as it spreads, but it also produces numerous and fragmented branches, or tendrils, at the swarm front. Whereas additional surfactants enhance swarming, increasing the agar percentage, adding extra salt or sugar or incorporating viscous agents in the agar matrix all decrease swarming, supporting the conclusion that swarming motility is restricted by the surface tension at the swarm front and swarm growth is limited by the rate of water supply from within the agar gel. The physical basis elaborated through this study provides a useful framework for understanding the swarming behavior of numerous species of bacteria.